Effects of Argonaute on Gene Expression in Thermus thermophilus. - Daan C Swarts (PLoS ONE, 2015)
Eukaryotic Argonaute proteins mediate RNA-guided RNA interference, allowing both regulation of host gene expression and defense against invading mobile genetic elements. Recently, it has become evident that prokaryotic Argonaute homologs mediate DNA-guided DNA interference, and play a role in host defense. Argonaute of the bacterium Thermus thermophilus (TtAgo) targets invading plasmid DNA during and after transformation. Using small interfering DNA guides, TtAgo can cleave single and double stranded DNAs. Although TtAgo additionally has been demonstrated to cleave RNA targets complementary to its DNA guide in vitro, RNA targeting by TtAgo has not been demonstrated in vivo.To investigate if TtAgo also has the potential to control RNA levels, we analyzed RNA-seq data derived from cultures of four T. thermophilus strain HB27 variants: wild type, TtAgo knockout (Δago), and either strain transformed with a plasmid. Additionally we determined the effect of TtAgo on expression of plasmid-encoded RNA and plasmid DNA levels.In the absence of exogenous DNA (plasmid), TtAgo presence or absence had no effect on gene expression levels. When plasmid DNA is present, TtAgo reduces plasmid DNA levels 4-fold, and a corresponding reduction of plasmid gene transcript levels was observed. We therefore conclude that TtAgo interferes with plasmid DNA, but not with plasmid-encoded RNA. Interestingly, TtAgo presence stimulates expression of specific endogenous genes, but only when exogenous plasmid DNA was present. Specifically, the presence of TtAgo directly or indirectly stimulates expression of CRISPR loci and associated genes, some of which are involved in CRISPR adaptation. This suggests that TtAgo-mediated interference with plasmid DNA stimulates CRISPR adaptation.